Optimized Transition from Inpatient Stroke Rehabilitation to Home Care - Current Practice and Analysis of Factors Influencing Transition - Saal, Susanne; Kirchner-Heklau, Uta; Müller, Tobias; Wohlfarth, Kai; Hamzei, Farsin; Müller, Melanie; Strobel, Susanne; Clewing, Carsten (Die Rehabilitation, 2019)
To identify factors influencing the current transition practice and to generate aspects to improve transition. Expert interviews and group discussions with health care professionals; a scoping review and a standardized interview with stroke patients 6 weeks after discharge via telephone. 14 expert interviews and 3 group discussions (n=18) were conducted. Factors influencing transition at home were communication of professionals between and within settings, social support and role behavior of stroke patients. The interviews (n=110) revealed realization of recommendations towards consultations of medical specialists of 37%, and of outpatient therapies up to 86%. The scoping review included 7 systematic reviews, 21 randomised trials and 5 controlled trials to patient education, information and counselling, Early Supported Discharge models, stroke liaison services, team conferences and integrated care pathways. A structured approach is needed which has to consider the complexity of the transition process.